Analisis Model AISAS dalam Menilai Efektivitas Brand Ambassador Asal Korea pada Aplikasi Mobile - Kurnia Khafidhatur Rafiah; Irsyad kamal; Amalis Karisma (Journal on Education, 2024)
The global phenomenon of the Korean wave, including its influence in Indonesia, has encouraged many businesses in Indonesia to employ Korean brand ambassadors as part of their marketing strategies, both for conventional and digital products. Previous studies, particularly those related to digital products, have shown negative responses, which motivated the author to conduct this research. This study focuses on three objects, namely Bukalapak, Ruangguru, and SimInvest, with the aim of evaluating and comparing the effectiveness of using Korean brand ambassadors for each application. The research employs a qualitative method with a survey approach to gather rich and diverse responses. The sampling technique used is quota sampling, with 30 participants for each research object. The results indicate that the use of Korean brand ambassadors is considered effective, although there are differences in effectiveness across several indicators, such as search and action.